Angiostatic factors in the pulmonary endarterectomy material from chronic thromboembolic pulmonary hypertension patients cause endothelial dysfunction. - Diana Zabini; Chandran Nagaraj; Elvira Stacher; Irene M Lang; Patrick Nierlich; Walter Klepetko; Akos Heinemann; Horst Olschewski; Zoltán Bálint; Andrea Olschewski (PLoS ONE, 2012)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare disease with persistent thrombotic occlusion or stenosis of the large pulmonary arteries resulting in pulmonary hypertension. Surgical removal of the neointimal layer of these vessels together with the non-resolved thrombus consisting of organized collagen-rich fibrotic areas with partly recanalized regions is the treatment of choice (pulmonary endarterectomy, PEA). The present study investigates endothelial cells isolated from such material as well as factors present in the surgical PEA material, which may contribute to impairment of recanalization and thrombus non-resolution. We observed muscularized vessels and non-muscularized vessels in the PEA material. The isolated endothelial cells from the PEA material showed significantly different calcium homeostasis as compared to pulmonary artery endothelial cells (hPAECs) from normal controls. In the supernatant (ELISA) as well as on the tissue level (histochemical staining) of the PEA material, platelet factor 4 (PF4), collagen type I and interferon-gamma-inducible 10 kD protein (IP-10) were detected. CXCR3, the receptor for PF4 and IP-10, was particularly elevated in the distal parts of the PEA material as compared to human control lung (RT-PCR). PF4, collagen type I and IP-10 caused significant changes in calcium homeostasis and affected the cell proliferation, migration and vessel formation in hPAECs. The presence of angiostatic factors like PF4, collagen type I and IP-10, as recovered from the surgical PEA material from CTEPH patients, may lead to changes in calcium homeostasis and endothelial dysfunction.